PENGARUH PROMOSI PENJUALAN KUPON MELALUI AKUN LINE@ DAN CITRA MEREK CALAIS TERHADAP MINAT PEMBELIAN ULANG KONSUMEN - Stefanie, Eoudia; ", Rumyeni (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
In the midst of intense business competition, marketers need the right marketing communication strategy to win consumer’s hearts. One of the strategy is by offering coupon sales promotion and support by brand image development. Both of these methods are proved capable to encourage consumer’s repurchase intention. Calais is one of the well-known bubble drink brand in Indonesia. This research is based on Stimulus-Response theory which describes communication as a simple action and reaction process, started from stimulus and ended with response. The purpose of this study is to find out whether Calais coupon sales promotion through LINE@ account and their brand image affect consumer’s repurchase intention or not.This research used explanative quantitative method. The data are collected using questionnaire with total sampel of 271 respondents taken using accidental random sampling technique. To know the influence of independent variables on dependent variable, the researcher use mutiple linear regression analysis, t-test, F-test and coefficient determination test. Meanwhile the questionnaire analysis is processed by using 16th version of SPSS program.This research measures coupon sales promotion variable through indicators: incentive size, participation conditions, promotion frequency, distribution media, and promotion time. Brand image variable is measured through indicators: brand identity, brand personality, brand association, brand behaviour & attitude and brand competence & benefit. As for repurchase intention is measured with transactional, referential, preferential and explorative intention indicators. Based on mutiple linear regression analysis, the regression equation is Y = 2,882 + 0,225 X1 + 0,470 X2. Through t-test and F-test, the significance value of each test is smaller than α = 0,05. Which means, all the alternative hypothesis which states there is influence created by Calais coupon sales promotion through LINE@ account and brand image towards repurchase intention are accepted, both partially and simultaneously. Coefficient determination test shows that the effect of Calais coupon sales promotion and brand image on consumer’s repurchase intention is 57,3%, which is a medium category. Meanwhile the remaining 42,7% is influenced by other factors beyond this study.Keyword: Coupon Sales Promotion, Brand Image, Repurchase Intention, Calais